PEMBUATAN ASAM GLUKONAT DARI GLUKOSA DENGAN PROSES FERMENTASI MENGGUNAKAN Aspergillus niger - Latifah, Ir; HP, Sudaryati; E, Hariyono (UPN VETERAN JAWA TIMUR, 2010)
Gluconic acid is a product of the dehydrogenation of glucose, and used widely industry. Gluconic acid which is crystallized in the form-δ-lactone glukono can be used to substitute for yeast in bread making and other food industries. The more 50,000 tons of gluconic acid were produced by fermentation using Aspergilus niger of material containing glucose. The purpose of this study to determine the best treatment volume and the fermentation time starter in the production of gluconic acid from glucose by fermentation with Aspergillus niger. This research used Completely Randomized Design (CRD) with factorial pattern consisting of 2 factors with 2 repetitions. The first factor is the length of fermentation (12 and 18, and 24 hours) and the second factor is the volume of starter (12, 16; and 20 mL) . The results showed that the best treatment there is the treatment of fermentation time 24 hours and the volume of 16 ml starter, which produces gluconic acid with a concentration = 7.405%, density = 1.1559 g / ml, pH = 3.4, biomass = 8.5580 gr .